A new generation of buses to support more sustainable urban transport policies: A path towards "greener" awareness among bus stakeholders in Europe. (June 2016) - Corazza, Maria Vittoria; Guida, Umberto; Musso, Antonio; Tozzi, Michele
Abstract: EBSF, 3iBS, ZeEUS, EBSF_2 and ELIPTIC are research projects funded by the European Commission, with the aim of developing a new generation of buses across Europe. For all, the common task is two-pronged (i) it is necessary to develop innovative solutions to increase the attractiveness of this mode and (ii) to operate more environmentally-friendly vehicles. Prototypes with more comfortable and accessible internal layouts, advanced ITS-based solutions, new engines designed to save fuel and eco-driving are key working areas. The environmental concern is behind the majority of the tested innovations. These projects are based on demonstrators, that is the innovative measures are tested in real urban environments. The assessment is a classical before-vs-during the implementation of measures comparison. A transferability study is aimed to assess the theoretical exportability of the tested measures across Europe. Results so far stressed contrasting aspects within a common vision for the development of a new generation of buses: although stakeholders are willing to innovate bus fleets by introducing more sustainable propulsion systems, conventional modes are still favoured and the environmental concern is not a driver to export the tested measures. The objectives of the paper are to describe such outcomes, identify reasons which prevent a wider exploitation of cleaner buses, provide possible explanations and suggest recommendations to develop "green" awareness among bus stakeholders. Highlights: A new generation of buses is needed to attract more demand to transit in Europe. Energy management, sustainability and appearance are main drivers for innovation. Operators seem to favour cleaner traction options, but not for environmental reasons. Costs of innovations are crucial in the decision process on the fleets upgrade. More research and funding can steer operators towards greener positions.